The Impact of Extension Services on Farm-level Income: An Instrumental Variable Approach to Combat Endogeneity Concerns - Cawley, Anthony; O’Donoghue, Cathal; Heanue, Kevin; Hilliard, Rachel; Sheehan, Maura (Applied economic perspectives and policy, 2018)
Agricultural extension is an important policy instrument utilized to diffuse knowledge and increase profitability among farmers. However, analyses on impact are subject to endogeneity concerns, causing multiple biases. Failure to combat endogeneity can lead to false inferences on impact. This article addresses this issue by applying an instrumental variable approach with distance to local advisory office and a policy change chosen as instruments for extension participation. The results show that participation significantly increased farm income and that OLS estimates underestimated the impact. Therefore, a superior estimate of impact is achieved which can be leveraged to better support accurate policy making.